DINAMIKA PERUBAHAN BAHASA INDONESIA DI ERA DIGITAL: - Manihuruk, Frido Evindey; Alisya, Jeane; Angka, Febriyanti; Lubis, Fitriani (Prawara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research examines the dynamics of Indonesian language change in a digitalized era, with a focus on the challenges faced by the younger generation in using social media. Indonesian has experienced significant changes along with globalization and the rapid progress of digital technology. This research uses qualitative methods and a descriptive approach. This research uses primary data in the form of a questionnaire which was distributed to 50 young generation respondents and mostly students from various universities. The results of this research show that social media has a big impact on changes in the Indonesian language. The younger generation is driving major changes in language as they become active users of social media. Finding a balance between language modernization and maintaining Indonesian language identity is the challenge.